BONUS BASMATI – Supporting maritime spatial planning with science. Deliverable 7.7 - Vesa Arki; Julia Ajanko; Hanna Luhtala; Harri Tolvanen (BONUS BASMATI - Baltic Sea Maritime Spatial Planning for Sustainable Ecosystem Services, 2022)
Overall, marine space is under increasing pressure from human activities. Traditionally, the activities taking place in oceans and seas were fishery and transport of goods and people. Today, offshore energy production, aquaculture, and sea-based tourism are important contributors to the global economy. This creates competition and conflicts between various uses and requires overall regulation and planning. Maritime activities generate pressures on the marine ecosystems, and in many areas severe impacts can be observed. Maritime spatial planning (MSP) is seen as an instrument to manage the seas and oceans in a more sustainable way, but to achieve this information and tools are needed.
BONUS BASMATI Project Findings presents the main results of the BONUS BASMATI project to the maritime spatial planning community, to relevant stakeholders, such as fishermen, environmental NGO’s, the offshore energy sector, the maritime traffic sector, and to the general public interested in sustainable use of the seas and oceans. The project outcomes will be presented under two main headlines: Concepts and approaches and Platforms and tools.
In order to address the need for integrated and innovative solutions for maritime spatial planning, BONUS BASMATI project has focused on the concepts and frameworks for decision support in maritime spatial planning. The outcomes include concepts for sustainability impact assessments of plan proposals related to marine and coastal ecosystem services and marine protected areas as well as a concept for data management. The chapter Framework for sustainability impact assessment of plan proposals, presents the BONUS BASMATI outcomes on how to assess the integrated social, economic, and environmental impacts of plan proposals for sustainable development of marine space. The chapter An ecosystem service approach to marine protected areas, presents a concept for designation of marine protected areas based on the value of the marine seabed habitats and their contribution to human wellbeing via the ecosystem services’ approach. The following chapter Data harmonisation facilitates planning across borders and scales presents a framework with effective steps towards a more coherent data management, which may foster better use of data in maritime spatial planning processes. Stakeholder involvement is essential for a proper maritime spatial planning process, and hence the chapter Involving stakeholders – Why, Who, When and How? addresses stakeholder involvement in the whole process of maritime spatial planning. The experiences of the Baltic Sea Region planners concerning how to address stakeholder involvement are presented, and how to involve the business sector is discussed as an example of a target group.
As part of the BONUS BASMATI project, digital decision support platforms and tools for maritime spatial planning have been developed, these will be presented in five chapters: 1) Baltic Explorer – new tools for collaboration 2) SPACEA – a GIS toolbox to facilitate easy spatial and environmental suitability analysis, 3) ESA4MSP – an ecosystem service assessment tool, 4) MYTILUS – a toolset for assessing the impacts of maritime activities, and 5) SEANERGY – a tool for analysing conflicts and synergies between different marine uses.